Social Norms, Labor Market Opportunities, and the Marriage Gap for Skilled Women - Marianne Bertrand; Patricia Cortes; Claudia Olivetti; Jessica Pan (Institute of Labor Economics (IZA), 2018)
In most of the developed world, skilled women marry at a lower rate than unskilled women. We document heterogeneity across countries in how the marriage gap for skilled women has evolved over time. As labor market opportunities for women have improved, the marriage gap has been growing in some countries but shrinking in others. We discuss the comparative statics of a theoretical model in which the (negative) social attitudes toward working women might contribute to the lower marriage rate of skilled women, and might also induce a non-monotonic relationship between their labor market prospects and their marriage outcomes. The model delivers predictions about how the marriage gap for skilled women should react to changes in their labor market opportunities across economies with more or less conservative attitudes toward working women. We verify the key predictions of this model in a panel of 26 developed countries, as well as in a panel of US states.
Keywords: J12; J16; 330; social norms; marriage gap; labor market opportunities